1917
DOI: 10.1021/ja02255a012
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Effect of the Partial Pressure of Oxygen on Combustion.

Abstract: from 95% alcohol, toluene and absolute alcohol, the bromide forms slightly brownish plates which soften above 129°a nd melt at 133-5 °. It is soluble in the cold in acetone or chloroform and sparingly so in alcohol, toluene, or ether. Kjeldahl: 0.3393 g. subst.; 12.7 cc. 0.1 N HC1.Calc, for CnHi402NBr: N, 5.15%. Found: N, 5.24%.^-Acetaminophenoxypropyl Cyanide (^-Acetaminophenyl-7-cyanopropyl Ether, p-Ac etaminophenoxybutyronitrile).-The cyanide was prepared as in the case of the ortho isomer, the yield from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1949
1949
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since former crewman William Alexander reported candle tests to determine the crew's oxygen supply [2], the estimated duration of the candle flame was also included in the calculations. Most sources report wick-fed flames extinguish in atmospheres of approximately 17%, with only one source indicating flames surviving as low as 15.7% oxygen [42][43][44]. It has also been observed that matches burn with difficulty in air when the CO 2 level exceeds 5% [41].…”
Section: (1)mentioning
confidence: 99%
“…Since former crewman William Alexander reported candle tests to determine the crew's oxygen supply [2], the estimated duration of the candle flame was also included in the calculations. Most sources report wick-fed flames extinguish in atmospheres of approximately 17%, with only one source indicating flames surviving as low as 15.7% oxygen [42][43][44]. It has also been observed that matches burn with difficulty in air when the CO 2 level exceeds 5% [41].…”
Section: (1)mentioning
confidence: 99%